2022
DOI: 10.17850/njg102-3-02
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the formation of sedimentary structures under antidunes using a 2D width-averaged numerical model

Abstract: A new numerical model for computing the formation of sedimentary structures in a fluvial environment is presented. The model has been used to explain the strata-forming processes under antidunes in detail, including water velocities, turbulence, free surface location, erosion, sedimentation and formation of each sediment layer. The Reynolds-Averaged Navier-Stokes equations were solved together with the k-epsilon turbulence model to determine the water flow field and the bed shear stress on a width-averaged two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Existing simulations of supercritical bedforms have mainly considered the Saint-Venant shallow-water equations (e.g. Parker & Izumi 2000;Balmforth & Vakil 2012) and the Reynolds-averaged Navier-Stokes approach to model cyclic steps (Vellinga et al 2018) or downstream-migrating antidunes (Olsen 2017(Olsen , 2022, but, to the best of the authors' knowledge, simulations of UMAs have not been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…Existing simulations of supercritical bedforms have mainly considered the Saint-Venant shallow-water equations (e.g. Parker & Izumi 2000;Balmforth & Vakil 2012) and the Reynolds-averaged Navier-Stokes approach to model cyclic steps (Vellinga et al 2018) or downstream-migrating antidunes (Olsen 2017(Olsen , 2022, but, to the best of the authors' knowledge, simulations of UMAs have not been reported so far.…”
Section: Introductionmentioning
confidence: 99%